The status of women in traditional kazakh society (Journal of Philosophy Culture and Political Science, 2018)
In Kazakhstan, from the period of independence, gender policy, the status of women, the family is an integral part of public policy. The main priorities identified in the strategy of gender equality in the Republic of Kazakhstan for 2006-2016 years/ woman in Kazakh society was the keeper of traditions and the family hearth and on an equal basis with men in economic, political and social life. Key words: Kazakhstan, traditional Kazakh society, status, woman, gender policy.